Trade Liberalisation in Sandalwood - Kushalapa, Kodira A. (Indian Forester, 1999)
Sandalwood (Santalum album) naturally occurs extensively in Southern States of India such as Karnataka, Tamil Nadu and Andhra Pradesh. It had export market from the period of Tipu Sultan or earlier for European and Mid-Eastern Countries and was therefore declared as "Royal Tree" in Karnataka. Special chapter exists in Karnataka Forest Act 1963 and Karnataka Forest Rules 1969, though nothing is mentioned in Indian Forest Act. Sandalwood is a Government property where ever it is found in Karnataka and therefore there are strict rules and regulations for its protection in and harvest from private lands; for its movement, trade and use. These are a deterrent for its existence and growth. People destroy its regeneration if found in their holdings. The declaration of bonus upto 75% of its value has not also encouraged its growing due to its inherent procedures and delays. There is a need for, rethinking and liberalising the existing rules, regulations and restrictions. The payment of bonus also needs simplification.